Investigation of ABO blood group expresser phenotype - Ó Donghaile, Diarmaid (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2011)
The aims of this project were to study the variability of the ABO blood group expression on human platelets and to explore the underlying molecular mechanisms. 541 Irish blood donors were studied. The recently described high and low expresser phenotypes of platelet ABO blood group were identified in 5.4% and 4.4% respectively in group A1 donors.
Keywords: Haemostasis Research Group, M.D.; M.D. Trinity College Dublin